Community Empowerment in Development in Sakita Village, Bungku Tengah District, Morowali Regency - Raehani Raehani; Slamet Riadi; Muhammad Ahsan Samad (Universitas Negeri Makassar, 2019)
This study aims to determine the process of community empowerment in development in Sakita Village, Bungku Tengah District, Morowali Regency. This study uses descriptive qualitative research type. This study uses theory (Elliot, 1996) to find out the stages in the process of community empowerment, there are 3 aspects that is, the welfare approach, the development approach and the empowerment approach. Data collection techniques are carried out through library research and field research. Which includes interview observation and documentation. There are 3 stages of qualitative data analysis namely data condensation, data presentation and conclusion drawing. Based on the research results obtained, it can be concluded that the quality of the welfare approach, development approach, and community empowerment approach in Sakita village, Bungku Tengah District, Morowali Regency have been implemented well. Although there are still many things that need to be improved by the village government together with the community.